Soilless culture technology to transform vegetable farming, reduce land pressure and degradation in drylands - Wolie Gebremicheal Gebreegziher (Cogent Food & Agriculture, 2023)
AbstractUse of farmlands for food production is under pressure and providing food for a growing population is a global concern due to alternative land use and degradation, pest infestations, urbanization and industrialization which led to climate change and encroaches arable land; especially in drylands where water, fertilizer, land, and other farm input resources are scares and needs to be utilized efficiently to enhance crop yields. Soilless culture technology reduces the challenges facing in soil-based farming which could lower yields. Improving food production and access could be possible using soilless culture. However, limited and incomplete information is available to indicate the role of soilless culture in reducing land pressure and degradation in drylands. This review aimed to examine the role of soilless culture as climate change occurs to transform dryland vegetable farming, reduce land pressure and degradation. Data gathered from relevant and recently published peer-reviewed papers and converted into uniform measurement units, paraphrased, and discussed. Studies indicated that soilless culture efficiently uses water, fertilizer, and land by 90, 70 and 75%, respectively, with average yield advantage of 147.3 t. ha−1 over soil-based farming. Soilless culture avoids soil disturbance and reduces land pressure and degradation while promoting crop intensification through year-round production. It supports soil-based farming, minimizes the negative impacts of agrochemicals on the environment, mitigates climate change, and increases productivity in drylands. It is economically feasible, environmentally sound, and socially accepted.